A Lysine Acetyltransferase Contributes to the Metabolic Adaptation to Hypoxia in Mycobacterium tuberculosis. Issue 12 (20th December 2018) - Rittershaus, Emily S.C.; Baek, Seung-Hun; Krieger, Inna V.; Nelson, Samantha J.; Cheng, Yu-Shan; Nambi, Subhalaxmi; Baker, Richard E.; Leszyk, John D.; Shaffer, Scott A.; Sacchettini, James C.; Sassetti, Christopher M.
Summary: Upon inhibition of respiration, which occurs in hypoxic or nitric oxide-containing host microenvironments, Mycobacterium tuberculosis (Mtb) adopts a non-replicating "quiescent" state and becomes relatively unresponsive to antibiotic treatment. We used comprehensive mutant fitness analysis to identify regulatory and metabolic pathways that are essential for the survival of quiescent Mtb. This genetic study identified a protein acetyltransferase (Mt-Pat/Rv0998) that promoted survival and altered the flux of carbon from oxidative to reductive tricarboxylic acid (TCA) reactions. Reductive TCA requires malate dehydrogenase (MDH) and maintains the redox state of the NAD+/NADH pool. Genetic or chemical inhibition of MDH resulted in rapid cell death in both hypoxic cultures and in murine lung. These phenotypic data, in conjunction with significant structural differences between human and mycobacterial MDH enzymes that could be exploited for drug development, suggest a new strategy for eradicating quiescent bacteria. Highlights: In Mtb, protein lysine acetylation promotes reductive TCA reactions in hypoxia Malate dehydrogenase (Mdh) is an essential component of the reductive TCA pathway Inhibition of Mdh causes rapid viability loss under hypoxic conditions and infection Structural comparisons suggest strategies for the design of specific Mdh inhibitors Abstract : Bacterial infections can persist because non-replicating organisms are killed slowly by antibiotics. This work describes a metabolic change that is essential for the survival of non-replicating Mycobacterium tuberculosis . Inhibition of the metabolic pathway favored under these conditions results in rapid death, suggesting a new strategy for accelerating therapy.